2012
DOI: 10.1002/j.2168-0159.2012.tb05872.x
|View full text |Cite
|
Sign up to set email alerts
|

50.3: Finite Element Analysis of Ball Drop on LCD Panels

Abstract: A ball drop test is amongst the tests used to assess the response of an LCD device under impact conditions. Two different glass thicknesses − 0.5 mm and 0.7 mm ‐ were submitted to this test in consideration for this paper. The result of the testing demonstrated that when a ball is dropped onto the outside surface of color‐filter glass, the peak stress occurs on the bottom of color‐filter glass, and not on the bottom of the TFT glass. In addition to this, we studied an extreme case where the back plate is rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…By comparing these three cases, it can be concluded that spacers and liquid crystal do not influence the global deformation of the panel. This conclusion is in line with references [ , which validate finite element models where spacers and liquid crystal were replaced with frictionless contact with experimental stress. Figure compares change in cell gap for the case where both spacers and liquid crystal were considered in the model with a case where only spacers were considered in the model.…”
Section: Resultssupporting
confidence: 90%
“…By comparing these three cases, it can be concluded that spacers and liquid crystal do not influence the global deformation of the panel. This conclusion is in line with references [ , which validate finite element models where spacers and liquid crystal were replaced with frictionless contact with experimental stress. Figure compares change in cell gap for the case where both spacers and liquid crystal were considered in the model with a case where only spacers were considered in the model.…”
Section: Resultssupporting
confidence: 90%
“…In some instances where the maximum deflection is restricted, thinner glass will experience lower bending stress than thicker glass and can be advantageous. 2) It is critical for the glass manufacturer to work closely with the panel and set manufacturers and designers to ensure the appropriate testing, criteria, and performance are met with ever-thinner glass and panels. 3)…”
Section: Display Panelmentioning
confidence: 99%
“…In fact, depending on the loading and boundary conditions, thin glass can sometimes have an advantage over thick glass. Figure 8 from reference [3] compares a panel made with 0.5 mm thick glass (0.5 mm CF and 0.5 mm TFT) and a panel made with 0.7 mm thick glass (0.7 mm CF and 0.7 mm TFT). It compares maximum stress experienced by the panels when a steel ball is dropped onto them.…”
Section: Device Designmentioning
confidence: 99%
“…This example demonstrates that device design plays an important role and sometimes it may be easier to change the device design and improve the reliability of the glass. Figure 8: Comparison of maximum principal stress for panels made with 0.7 mm and 0.5 mm thick glass sheets [3]. Also shown is a comparison between having a back plate at a distance of 2.8 mm from surface-4 and not having a back plate.…”
Section: Device Designmentioning
confidence: 99%
See 1 more Smart Citation